the NOMINAL ELLIPSIS IN THE STORY OF “THE BOYHOOD OF RONGGOWARSITO”: NOMINAL ELLIPSIS IN THE STORY OF “THE BOYHOOD OF RONGGOWARSITO” - Putu Eka Suardana (Universitas Bali Dwipa, 2021)
This study entitled Nominal Ellipsis in the Story of “The Boyhood of Ronggowarsito” aimed at analyzing and classifying the classification of the kinds of nominal ellipsis in English textbooks particularly in each text. The primary data was taken from the English textbooks: The Boyhood of Ronggowarsito (1991).The main theory used in this study was taken from a book entitled Cohesion in English (1975) by M.A.K Halliday and Ruqaiya Hasan. They stated that ellipsis is the omission of an item of a sentence on the assumption which an earlier sentence will make the meaning clear. They classify ellipsis into three types: nominal ellipsis, verbal ellipsis and clausal ellipsis. The required data were classified and analyzed based on the classification of nominal ellipsis. Nominal ellipsis consisted of the elements of deictic, numerative, epithet, classifier and qualifier and also the head. Nominal ellipsis consisted of modal element and propositional element. The findings showed that the type of nominal ellipsis must be the common noun and not proper noun or pronoun expressing the thing. The common noun created the functions of the element of deictic, numerative, epithet and classifier and these elements can function as head under certain circumstances.